Modeling the isothermal inactivation curves of Listeria innocua CECT 910 in a vegetable beverage under low-temperature treatments and different pH levels. (September 2016) - Vega, Sandra; Saucedo, Daniela; Rodrigo, Dolores; Pina, Consuelo; Armero, Carmen; Martínez, Antonio
Thermal inactivation kinetics of Listeria innocua CECT 910 inoculated in a vegetable beverage at three pH conditions (4.25, 4.75, and 5.20), four levels of temperature (50, 55, 60, 65℃), and different treatment times (0–75 min) were obtained. Survival curves did not follow a log-linear relationship and consequently were fitted to various mathematical models: Weibull, Geeraerd, Cerf with shoulder, and the modified Gompertz equation. Results indicated that the best model for the treatment conditions was the modified Gompertz equation, which provides the best goodness-of-fit and the lowest Akaike information criterion value. Sensitivity analysis indicated that the most influential factors affecting the final microbial load were temperature and time in the case of the higher temperature level (65℃) and time in the case of the lower temperature level (50℃).